Remote Pyramid-Shaped Phosphor Coating for Phosphor-Converted White LEDs - (:unkn) unknown (Scientific research, 2017)
Increasing light extraction efficiency is an important task when it comes to manufacturing a powerful white light emitting diode with high luminous flux per watt. In this paper the fabrication of a pyramid-shaped 3-dimensional phosphor coating is reported. It is represented by a phosphor cover, shaped into an array of pyramid like formations. It is proposed that such a structure can improve the light extraction efficiency and the color distribution characteristics of any phosphor-converted white LED. The luminous flux and luminous efficacy are being studied as a function of the forward current across the die. It was found out that with this kind of technique it was possible to achieve an 8% - 14% increase in the efficacy of the pc-LED. This increase of light output power is being attributed to the reduction of the phenomena of total internal reflection (TIR) inside the packaging module
Keywords: Light Emitting Diode (LED); Chip-On Board (COB) Package; Light Extraction Efficiency; Total Internal Reflection (TIR)